1994
DOI: 10.1007/bf02578242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary carnosine on plasma and tissue antioxidant concentrations and on lipid oxidation in rat skeletal muscle

Abstract: The effect of dietary carnosine supplementation on plasma and tissue carnosine and alpha-tocopherol concentrations and on the formation of thiobarbituric acid reactive substances (TBARS) in rat skeletal muscle homogenates was evaluated. Plasma, heart, liver and hind leg muscle was obtained from rats fed basal semipurified diets or basal diets containing carnosine (0.0875%), alpha-tocopheryl acetate (50 ppm), or carnosine (0.0875%) plus alpha-tocopheryl acetate (50 ppm). Dietary carnosine supplementation did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 28 publications
2
25
1
1
Order By: Relevance
“…This state may account for the synergistic effect of the combined use of CAT and Vit E. This combination was detected to be more effective in decreasing the lipid peroxides in liver and heart tissues of rats than dietary CAR or Vit E alone. 30,31,35 In the current study, no amelioration was observed in the disturbed serum and tissue Figure 1. The effect of CAR þ Vit E treatments on DOX-induced histopathological alterations in the heart, liver, and kidney tissues (H&E).…”
Section: Discussionmentioning
confidence: 49%
“…This state may account for the synergistic effect of the combined use of CAT and Vit E. This combination was detected to be more effective in decreasing the lipid peroxides in liver and heart tissues of rats than dietary CAR or Vit E alone. 30,31,35 In the current study, no amelioration was observed in the disturbed serum and tissue Figure 1. The effect of CAR þ Vit E treatments on DOX-induced histopathological alterations in the heart, liver, and kidney tissues (H&E).…”
Section: Discussionmentioning
confidence: 49%
“…(2005) showed that hydrolysis of the dipeptide by carnosinase in plasma might mean that carnosine may not be taken up by skeletal muscles. Chan et al. (1994b) reported that feeding a diet containing supplemental carnosine (875 mg/kg diet) decreased the formation of thiobarbituric acid‐reactive substances in rat skeletal muscle, but did not increase the carnosine level in muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Carnosine is found in the brain, heart, skin, liver, kidney, and skeletal muscle of various animals [Chan et al (1994); Crush (1970)]. Skeletal muscle in particular contains a high quantity of carnosine.…”
Section: Discussionmentioning
confidence: 99%